Excess Mortality associated to Influenza epidemic in Portugal, from 2007/2008 to 2014/2015 seasons - Silva, Susana Pereira (2016)
Mortality in the north hemisphere is higher in winter than in summer seasons, due to the influenza epidemics as well as cold temperatures. Portuguese influenza surveillance comprises clinical and laboratorial notifications of Influenza-like Illness (ILI) attended in the primary health care units and emergency rooms. Without information on specific cause of deaths in real time, estimation of influenza impact has been accessed using Portuguese Daily Mortality Monitoring System (VDM), that covers all cause mortality of Portuguese population. The aim of this study was to provide excess mortality, potentially associated to Influenza each season (between 2007/08 and 2014/15).